2008
DOI: 10.1210/jc.2008-1189
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Dominant Negative Mutation of OTX2 Associated with Combined Pituitary Hormone Deficiency

Abstract: A novel mutation in OTX2 binds normally to target genes and acts as a dominant negative inhibitor of HESX1 gene expression. This suggests that the expression of HESX1, required for spaciotemporal development of anterior pituitary cell types, when disrupted, results in an absent or underdeveloped anterior pituitary with diminished hormonal expression. These results demonstrate a novel mechanism for CPHD and extend our knowledge of the spectrum of gene mutations causing CPHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
92
2
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(100 citation statements)
references
References 45 publications
3
92
2
3
Order By: Relevance
“…An ectopic or undescended posterior pituitary lobe is also a frequent finding in patients with GH deficiency, especially CPHD. Its presence on MRI has been increasingly used for the diagnosis of (Diaczok et al 2008, Dateki et al 2010. In addition, mutations in these early acting factors may present as part of a syndrome in patients that manifest abnormalities in extra-pituitary structures that share a common embryological origin with the pituitary gland, such as the eye and forebrain.…”
Section: Human Mutationsmentioning
confidence: 99%
“…An ectopic or undescended posterior pituitary lobe is also a frequent finding in patients with GH deficiency, especially CPHD. Its presence on MRI has been increasingly used for the diagnosis of (Diaczok et al 2008, Dateki et al 2010. In addition, mutations in these early acting factors may present as part of a syndrome in patients that manifest abnormalities in extra-pituitary structures that share a common embryological origin with the pituitary gland, such as the eye and forebrain.…”
Section: Human Mutationsmentioning
confidence: 99%
“…Therefore, it is possible that in response to SHH signalling, GLI proteins activate other target genes directly involved in pituitary organogenesis (Franca et al 2010). Otx2 is another TF that is not expressed in the pituitary tissues themselves (Diaczok et al 2008, Gorbenko Del Blanco et al 2012. This TF encodes a bicoid protein that is important for eye and forebrain formation (Schilter et al 2011, Gorbenko Del Blanco et al 2012.…”
Section: Early Organogenesis: Rathke's Pouch Invaginationmentioning
confidence: 99%
“…This TF encodes a bicoid protein that is important for eye and forebrain formation (Schilter et al 2011, Gorbenko Del Blanco et al 2012. OTX2 is also responsible for Hesx1 expression regulation (Diaczok et al 2008). Hesx1 is the first pituitary-specific TF to be expressed at or before E6 .…”
Section: Early Organogenesis: Rathke's Pouch Invaginationmentioning
confidence: 99%
See 1 more Smart Citation
“…The Sine oculis homeobox homolog (Six) gene family encodes a group of transcription factors that is related to homeobox-containing gene product in vertebrates by two conserved domains (Conte et al, 2005;Diaczok et al, 2008;Weasner and Kumar, 2009). Previous studies have reported that the Six family plays an important role in the entire development of the fly's visual system (Cheyette et al, 1994;Jean et al, 1999).…”
Section: Introductionmentioning
confidence: 99%